FAKTOR-FAKTOR YANG MEMPENGARUHI PERUBAHAN FUNGSI EKSTREMITAS BAWAH DAN PSIKOLOGIS SEBELUM DAN SESUDAH OPERASI ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION: Abstrak, Pendahuluan, Metode Penelitian, Hasil, Pembahasan, Simpulan, Daftar Pustaka - Ni Nyoman Rinda Pravidayanti; I Putu Gde Surya Adhitya; Anak Agung Gede Eka Septian Utama (PT. Kesehatan Gerak Fungsi Tubuh, 2023)
Background: The Anterior Cruciate Ligament (ACL) is a type of ligament situated within the human knee joint, connecting the femur to the tibia. It plays a crucial role in maintaining joint stability and controlling the anterior movement of the tibia relative to the femur. ACL reconstruction is a surgical procedure to connect the ACL ligament to restore stability to knee function. In performing reconstruction, factors will affect the reconstruction results, one of which is the provision of rehabilitation, which will affect the patient's knee injury and osteoarthritis outcome score (KOOS). Another factor, kinesiophobia, can affect psychologically, so patients tend to feel afraid to move. Objective: To determine whether factors affect lower extremity function and psychology before and after anterior cruciate ligament reconstruction (ACLR) surgery. Methods: The study used a literature review design where the secondary data from published literature was reviewed and reported as the study topic. Literature searches were conducted online from PubMed and Google Scholar, using the keywords